Nursing Care for Mrs. R with Urinary System Disorders: Chronic Kidney Disease in the Inpatient Room of Royal Prima Hospital Medan in 2026 - Rodi Saputra Buulolo; Tamara Angelina Hutagaol; Rina Aprina; Al Furqan; Samahuwu Buulolo; Afeus Halawa (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Background: Chronic Kidney Disease (CKD) is a progressive and irreversible impaired kidney function, causing various health problems such as urinary elimination disorders, hypervolemia, electrolyte imbalance, and an increased risk of infection. Patients with late-stage CKD generally require hemodialysis therapy to maintain body function and prevent further complications. Objective: To describe the implementation of nursing care in patients with urinary system disorders due to Chronic Kidney Disease undergoing hemodialysis therapy. Methods: Case studies with a nursing process approach that includes assessment, nursing diagnosis, planning, implementation, and evaluation. The subject of the study is Mrs. R, a stage V CKD patient who is undergoing treatment in the inpatient room of Royal Prima Medan Hospital in 2026. Data was obtained through interviews, observations, physical examinations, and medical record documentation studies. Results: The results of the study showed that the patient had severe oliguria (±100 ml/24 hours), edema in both legs, hypertension, increased urea and creatinine levels, and electrolyte balance disorders. Established nursing diagnoses include urinary elimination disorders, hypervolemia, risk of electrolyte imbalance, and risk of infection. The implementation of nursing was carried out for three days through monitoring fluid status, urine elimination, electrolyte balance, infection prevention, fluid restriction education, low-potassium diet, and hemodialysis therapy collaboration. Evaluation showed that there was an improvement in the patient's condition characterized by reduced edema, more stable blood pressure, decreased potassium levels, and no signs of infection in hemodialysis vascular access. Conclusion: Comprehensive nursing care for CKD patients undergoing hemodialysis is able to help control fluid and electrolyte balance, reduce symptoms of hypervolemia, improve patient understanding of the disease, and prevent complications during treatment.